The lower pleistocene Arda river invertebrate fauna : palaeoecology, palaeoclimatology and biochronology - G. Crippa; F. Felletti; G. Raineri (Rendiconti Online della Società Geologica Italiana, 2014)
The Arda River succession, cropping out in Western Emilia, Northern Italy, is a marine succession of Early Pleistocene age; it is composed mainly of sandstones, siltstones and claystones and it is bounded at its top by continental conglomerates, representing a major sea level drop and the establishment of a continental environment with vertebrate faunas and fresh water molluscs. Numerous fossiliferous levels very rich in macroinvertebrates are present along the marine succession; the very diverse fauna comprises bivalves, brachiopods, gastropods, corals, serpulids, bryozoan, echinoderms, scaphopods and barnacles. Fossils are generally well preserved with several articulated specimens in life position and often preserving the color and the spiny fragile ornamentation. The results of the analysis of the faunal association are the following: Palaeoecologic implication. The Arda fauna is characterized by both infaunal and epifaunal species, mainly of infra- and circalittoral environment. The higher biodiversity has been recorded in fine sandstones, which contain the typical shallow water association with Chamelea gallina, Acanthocardia tubercolata and Glycymeris insubrica; a lower biodiversity has been instead recorded in siltstones barren of sedimentary structures and characterized by a deeper water fauna, mainly typified by the bivalve Venus multilamella and the gastropod Turritella tricarinata. The palaeoecological analysis of the fauna confirms the general regressive trend of the marine succession; several alternation of lower order transgressive and regressive sedimentary cycles are present, but no event of emersion or shift to very deep water setting has been recorded. Palaeoclimatic implication. The occurrence of boreal guests, such as Arctica islandica, Pseudamussium septemradiatum, Mytilus edulis and Acanthocardia echinata, suggests that a climatic change occurred in the section causing a shift from warm to cold seawater temperatures. The evolution of this climatic deterioration is complex, but it prepares ...